Factors affecting BIM implementation: evidence from countries with different income levels - Al-Mohammad, Mohammad S.; Ahmad Tarmizi, Haron; Esa, Muneera; Aloko, Mohammad Numan; Alhammadi, Yasir; K. S., Anandh; Rahimi, A. Rahman (Amerald, 2022)
Purpose: This study aims to empirically analyze the symmetries and asymmetries among the critical factors affecting building information modeling (BIM) implementation between countries with different income levels. To achieve that aim, the study objectives are to identify: critical factors affecting BIM implementation in low-, lower-middle-, upper-middle- and high-income countries; overlapping critical factors between countries with different income levels; and agreements on the critical factors between countries with different income levels.